1988
DOI: 10.1159/000184914
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels and Loss of Antithrombin III in Chronic Ambulatory Peritoneal Dialysis and Nephrotic Patients

Abstract: Plasma antithrombin III (AT III) levels were measured as antigen concentration (radial immunodiffusion) and as heparin cofactor (amidolytic method) in 9 patients on continuous ambulatory peritoneal dialysis (CAPD). The loss of albumin, proteins, AT III antigen and AT III functional activity was calculated from the peritoneal dialysate and the corresponding serum levels were measured. The same determinations were performed on serum and urinary samples from 9 patients with nephrotic syndrome. Mean plasma levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Clinical data of turnover of these natural coagulation inhibitors in CAPD patients are limited. Mori et al [24] had reported a normal plasma levels of AT III antigen and AT III heparin cofactor in 9 CAPD patients despite loss of AT III through the peritoneal dialysate. Most AT III in the peritoneal dialysate from CAPD patients were still active in contrast to only 26% in urinary AT 111 lost by nephrotic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical data of turnover of these natural coagulation inhibitors in CAPD patients are limited. Mori et al [24] had reported a normal plasma levels of AT III antigen and AT III heparin cofactor in 9 CAPD patients despite loss of AT III through the peritoneal dialysate. Most AT III in the peritoneal dialysate from CAPD patients were still active in contrast to only 26% in urinary AT 111 lost by nephrotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most AT III in the peritoneal dialysate from CAPD patients were still active in contrast to only 26% in urinary AT 111 lost by nephrotic patients. The quantity of protein lost through the dialysate in patients on CAPD is considerable and is often comparable to that of nephrotic patients as calcu lated by measuring daily proteinuria (24,25]. Hence, one would predict continuous losses of PC, PS, and AT III through the peritoneal dialysate in patients receiving CAPD, which could lead to low plasma levels and in creased risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Gries et al [14] sug gested that higher AT 111 proportion of total protein in dialysate than in plasma may be more important for a sufficient inhibition of intraperitoneal thrombin activity in heparinized dialysate than the absolute concentration. Mori et al [15] reported that almost all of the AT III antigen found in the dialysate maintained its heparin cofactor activity in CAPD patients. Recently, Gries et al [16] reported that the application of 500 U/l of heparin was enough to inhibit the intraperitoneal fibrin forma tion and in 2 patients fibrin formation was suppressed even during peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…It is the principal inhibitor of thrombin, activated factors IX, X, XI and XII, and plasmin. 25,26 More than 90% of patients with nephrotic syndrome and documented thromboembolic phenomena have been shown to have antithrombin III levels that are less than 75% of normal. 20 The mechanism responsible for the subnormal serum or plasma levels of this protein has not yet been clarified.…”
Section: Coagulation Inhibitorsmentioning
confidence: 99%
“…20 The mechanism responsible for the subnormal serum or plasma levels of this protein has not yet been clarified. Because antithrombin III has been detected in the urine of nephrotic patients, 26 it is conceivable that either increased urinary losses or enhanced renal tubular catabolism of this protein could play an important role in this regard.…”
Section: Coagulation Inhibitorsmentioning
confidence: 99%